2012
DOI: 10.1590/s0100-879x2012007500035
|View full text |Cite
|
Sign up to set email alerts
|

REGγ is a strong candidate for the regulation of cell cycle, proliferation and the invasion by poorly differentiated thyroid carcinoma cells

Abstract: REGγ is a proteasome activator that facilitates the degradation of small peptides. Abnormally high expression of REGγ has been observed in thyroid carcinomas. The purpose of the present study was to explore the role of REGγ in poorly differentiated thyroid carcinoma (PDTC). For this purpose, small interfering RNA (siRNA) was introduced to down-regulate the level of REGγ in the PDTC cell line SW579. Down-regulation of REGγ at the mRNA and protein levels was confirmed by RT-PCR and Western blot analyses. FACS an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…REGc is highly expressed in many cancers including the breast cancer [6][7][8][9][10]. One possibility is that the high expression of REGc is a bi-product and has little effect on cancer growth.…”
Section: Cell Proliferation Mobility and Invasion Ability Is Signifmentioning
confidence: 99%
See 1 more Smart Citation
“…REGc is highly expressed in many cancers including the breast cancer [6][7][8][9][10]. One possibility is that the high expression of REGc is a bi-product and has little effect on cancer growth.…”
Section: Cell Proliferation Mobility and Invasion Ability Is Signifmentioning
confidence: 99%
“…It can stimulate the proteolytic activity of 20S proteasome and enable protein/peptide substrates to diffuse into the environment of proteasomes [4,5]. REGc has been reported to be highly expressed in human breast cancers [6,7], thyroid cancers [8], hepatocellular carcinomas [9] and colorectal cancers [10]. In addition, recent studies have showed that REGc play a role in protein degradation of tumor suppressor p53 [11,12], oncogene steroid receptor coactivator-3 (SRC-3) [13], as well as cell cycle regulator proteins including p21, p16 and p19 [14].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the expression of REGγ has been found abnormally high in human breast cancer cells and the metastatic lymph nodes (Wang et al, 2009). Recently, there has study showed that REGγ was a strong candidate for the regulation of cell cycle, proliferation and the invasion in poorly differentiated thyroid carcinoma cells (Zhang et al, 2012). Despite these interesting observations, the pathological contributions of the REGγ to the development of cancer remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…REGγ, also known as proteasome activator subunit 3, is an ATP-and ubiquitin-independent proteasome activator [6]. It is evident that REGγ is involved in the progression of cancers [7,8].…”
Section: Introductionmentioning
confidence: 99%